Urban Cascadia and the pursuit of environmental justice - Janos, Nik; McKendry, Corina (University of Washington Press, 2021)
"Urban Cascadia-roughly, the Portland, Seattle, and Vancouver corridor-enjoys a reputation for progressive ideals and forward-thinking green urbanism. Yet there is more to the region's environmental politics that meet the eye. Nik Janos and Corina McKendry propose an edited collection that examines the environmental transformation of these cities, using a critical lens on the surrounding myths and imaginaries to probe underlying structural inequalities and contradictions. In particular, contributors across disciplines (but along a nexus of geography, sociology, and history) seek to better understand the capitalist urbanization of nature, the creation of social and environmental inequalities, and the movements to fight for social and environmental justice. The goal isn't to debunk the region's image or offer a story of green boosterism. But by grappling with the contradictions of the urbanization of Cascadia, they hope to offer insight on sustainability, social justice, urban governance, and the politics of climate change. The idea to offer a one-stop assessment for those interested in the region, and to push for a more critical approach to narratives about sustainability"--